Panggilan Misi di Indonesia: Strategi Penjangkauan Jiwa yang Belum Terjangkau Injil - Anita Mariana Parulian Butar-Butar (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2025)
In this article, the author is highlighting the urgency of the mission call of the church of God as a divine mandate and the destiny (purpose) of His church in carrying out the Great Commission of the Lord Jesus in Indonesia. Based on the theological foundation of missio Dei, starting from the call of Abraham (Gen. 12: 1–3) and the Great Commission of Christ (Matthew 28: 18–20). The focus of this study is the response to the mission call to reach souls who have not been reached by the Gospel through a number of theological understandings of the mission call, mission strategies and their application to churches and mission institutions in Indonesia. The mission to unreached tribes also plays a role in God's global plan of salvation. Churches, theological institutions, and mission servants are encouraged to be actively and collaboratively involved in the ongoing mission call for holistic transformation and fulfillment of the mission of the Lord Jesus.